Recruiting International Students to Your Campus - McFadden, Cheryl; Maahs-Fladung, Cathy; Mallett, William (Journal of International Students, 2012)
The purpose of this paper was to determine what institutional, program, and recruitment characteristics influenced international students to attend institutions in the United States. Two hundred sixteen international students at a Southern public research university responded to the survey (53% response rate) from 56 countries representing 8 regions. An empirical analysis using t-tests and analysis of variance was conducted to determine what characteristics international students found to be most important when selecting an institution. Regardless of degree level, all students ranked faculty/student ratio as an important program characteristic. Second, students ranked both the admission process and time to degree as important characteristics. Third, doctoral, master’s, and bachelor’s students respectively ranked funding as an important characteristic in their decision making process. There are three basic implications for recruitment officers. First, as size matters, international students need to feel connected to faculty and staff.